The self-perception of dental aesthetics and smile in students the faculty of medicine: Studi cross-sectional - Sari, Mayang Anggita; Irsal, Imran; Pramulia Yudia, Riries Choiru (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRACTIntroduction: Dental aesthetics and smiles play an important role in shaping a person's perception of their own appearance and that of others. This study was conducted to determine the perception of dental aesthetics and smiles among medical students, as factors such as age, gender, and educational level can influence a person's aesthetic judgment. Methods: This study is a descriptive study with a cross-sectional design. The study utilized a questionnaire comprising 15 questions using the Gutmann scale, with response options of YES or NO. Data collection was conducted in November 2022. The study respondents were 201 medical students, selected using stratified random sampling. The responses selected by the respondents were analyzed using descriptive statistics. Results: Respondents aged 22 years had the highest positive perception at 75.0%, while the lowest percentage was among respondents aged 17 years at 40.0%. Male respondents had a more positive self-perception at 70.7%, while female respondents had 47.6%. Based on academic level, respondents in their fourth year (class of 2019) had a positive perception of 71.4%, while respondents in their first year (class of 2022) had a positive perception of 38.8%. Students from the Dentistry Program had the highest percentage based on educational background, at 59.4%. Conclusion: The highest positive perception was among respondents aged 22 years. Male respondents had a more positive perception. Based on academic level, the highest positive perception was among respondents with a higher academic level, and based on educational background, the highest positive perception was among respondents from the Dental Medicine Program.KEY WORDS: Self-Perception, dental aesthetics, smile aesthetics, smile, academicPersepsi Estetika Gigi dan Senyum pada Mahasiswa Fakultas Kedokteran : Studi cross-sectionalABSTRAK Pendahuluan: Estetika gigi dan senyum memainkan peranan penting dalam membentuk persepsi seseorang terhadap penampilan dirinya maupun orang lain. Penelitian ini dilakukan bertujuan untuk mengetahui persepsi estetika gigi dan senyum pada Mahasiswa Fakultas Kedokteran, karena faktor seperti usia, jenis kelamin dan tingkat pendidikan dapat mempengaruhi penilaian estetika seseorang. Penelitian ini bertujuan untuk mengetahui persepsi estetika gigi dan senyum pada Mahasiswa Fakultas Kedokteran. Metode: Penelitian ini merupakan penelitian deskriptif dengan desain penelitian cross-sectional. Penelitian ini menggunakan kuesioner yang memuat 15 pertanyaan dengan menggunakan skala Guttman dengan alternatif pertanyaan YA atau TIDAK. Pengambilan data dilaksanakan pada bulan November 2022. Responden penelitian mahasiswa Fakultas Kedokteran yang berjumlah 201 mahasiswa dan menggunakan teknik stratified random sampling. Jawaban yang dipilih responden dianalisis menggunakan metode descriptive statistics. Hasil: Responden dengan usia 22 tahun memiliki persepsi positif dengan persentase tertinggi yaitu 75.0%, persentase terendah yaitu pada responden dengan usia 17 tahun hanya 40.0%. Responden laki-laki lebih memiliki persepsi diri yang positif yaitu 70.7% dan responden perempuan hanya 47.6%. Mahasiswa berdasarkan tingkat akademik, responden tingkat 4: angkatan 2019 memiliki persepsi diri positif yaitu 71.4% dan pada responden tingkat 1: angkatan 2022 sebanyak 38.8% dan Program Studi Kedokteran Gigi memiliki persentase tertinggi berdasarkan latar belakang pendidikan responden, yaitu sebanyak 59.4%. Simpulan: Persepsi positif paling banyak adalah pada responden yang dengan usia 22 tahun. Responden laki-laki memiliki persepsi yang lebih positif. Berdasarkan tingkat akademik, persepsi positif paling banyak adalah pada responden dengan tingkat akademik yang lebih tinggi, dan berdasarkan latar belakang pendidikan, persepsi positif paling banyak adalah pada responden Program Studi Kedokteran Gigi.KATA KUNCI: Persepsi diri, estetika gigi, estetika senyum, senyum, pendidikan